Sexuality as Sacrament: An Evangelical Reads Andrew Greeley - Blair, Anthony L. (Theology today, 2010)
Andrew M. Greeley, a noted sociologist and Catholic priest, has also established a reputation as a writer of racy novels. In these stories, he portrays sexuality as sacrament, a means of grace whereby the love of God is experienced via physical and emotional intimacy between the sexes. While there are some weaknesses to his approach, his emphasis on strong female characters and a sacralizing sexuality are ultimately a positive contribution to our culture's struggles with love, sex, and intimacy.